Bisnis Herbalife Nutrition Club Cupid Ceria Perspektif Fatwa DSN-MUI NO.75/DSN MUI/VII/2009 - Arik Putri Lestari, Yosy; Rofiah, Khusniati (Institut Agama Islam Negeri Ponorogo, 2021)
The purpose of this study was to find out how the perspective of the DSN MUI fatwa No.75 / DSN MUI / VII / 2009 on PLBS on Herbalife business practices at the Nutrition Club Cupid Ceria Madiun City related to price, royalty, and the concept of ighra'. This research uses field research methods with a qualitative approach. The results of this study can be seen that 1) The price of Herbalife products is not following the DSN MUI fatwa No.75 / DSN MUI / VII / 2009 concerning PLBS because it is included in the Excessive Markup category because the product price is relatively high and does not match the profit-sharing 2) Royalty in the Herbalife bonus system is fully following the DSN MUI fatwa No.75 / DSN MUI / VII / 2009 regarding PLBS because bonuses are the result of actual work, the amount is precise, not passive income and there is no exploitation or injustice. 3) Royalty in business Herbalife is also following the DSN MUI fatwa No.75 / DSN MUI / VII / 2009 regarding PLBS, which is not included in the ighra ' category because initially businessmen are not immediately interested in bonuses in this business but are only interested in the product results they want to achieve